Global prevalence of non-alcoholic fatty liver disease and non-alcoholic steatohepatitis in the overweight and obese population: a systematic review and meta-analysis. (January 2023) - Quek, Jingxuan; Chan, Kai En; Wong, Zhen Yu; Tan, Caitlyn; Tan, Bryan; Lim, Wen Hui; Tan, Darren Jun Hao; Tang, Ansel Shao Pin; Tay, Phoebe; Xiao, Jieling; Yong, Jie Ning; Zeng, Rebecca Wenling; et al.
Summary: Background: The global burden of non-alcoholic fatty liver disease (NAFLD) parallels the increase in obesity rates across the world. Although overweight and obesity status are thought to be an effective indicator for NAFLD screening, the exact prevalence of NAFLD in this population remains unknown. We aimed to report the prevalence of NAFLD, non-alcoholic fatty liver (NAFL), and non-alcoholic steatohepatitis (NASH) in the overweight and obese population. Methods: In this systematic review and meta-analysis, we searched Medline and Embase from database inception until March 6, 2022, using search terms including but not limited to "non-alcoholic fatty liver disease", "overweight", "obesity", and "prevalence". Cross-sectional and longitudinal observational studies published after Jan 1, 2000, written in or translated into English were eligible for inclusion; paediatric studies were excluded. Articles were included if the number of NAFLD, NAFL, or NASH events in an overweight and obese population could be extracted. Summary data were extracted from published reports. The primary outcomes were the prevalence of NAFLD, NAFL, and NASH in an overweight and obese population and the prevalence of fibrosis in individuals who were overweight or obese and who had NAFLD. A meta-analysis of proportions was done with the generalised linear mixed model. This study is registered with PROSPERO (CRD42022344526). Findings: The search identified 7389 articles. 151 studies met the inclusion criteria and were included in the meta-analysis. In the pooled analysis comprising 101 028 individuals, the prevalence of NAFLD in the overweight population was 69·99% (95% CI 65·40–74·21 I 2 =99·10%), the prevalence of NAFL was 42·49% (32·55–53·08, I 2 =96·40%), and the prevalence of NASH was 33·50% (28·38–39·04, I 2 =95·60%). Similar prevalence estimates were reported in the obese population for NAFLD (75·27% [95% CI 70·90–79·18]; I 2 =98·50%), NAFL (43·05% [32·78–53·97]; I 2 =96·30%) and NASH (33·67% [28·45–39·31]; I 2 =95·60%). The prevalence of NAFLD in the overweight population was the highest in the region of the Americas (75·34% [95% CI: 67·31–81·93]; I 2 =99·00%). Clinically significant fibrosis (stages F2–4) was present in 20·27% (95% CI 11·32–33·62; I 2 = 93·00%) of overweight individuals with NAFLD and in 21·60% (11·47–36·92; I 2 =95·00%) of obese patients with NAFLD while 6·65% (4·35–10·01; I 2 =58·00%) of overweight individuals with NAFLD and 6·85% (3·85–11·90; I 2 =90·00%) of obese individuals with NAFLD had advanced fibrosis (stages F3–4). Interpretation: This study summarises the estimated global prevalence of NAFLD, NAFL, and NASH in overweight and obese individuals; these findings are important for improving the understanding of the global NAFLD burden and supporting disease management in the at-risk overweight and obese population. Funding: None.